Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan - Sulbahri, Rifani Akbar (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
This study aims to examine the effect of corporate social responsibility (CSR) on firm value. The analysis technique used is regression analysis Simple Based on the test results, the conclusions that can be drawn from this research arethat the results of the study indicate that the Corporate social responsibility variable has a significant effect on the value of the company with a value of prob. Corporate social responsibility variable < critical probability value (a = 5%) of 0.027 <0.05, so that the Corporate social responsibility variable has a significant effect on firm value. The conclusion is that corporate social responsibility has a significant effect on firm value in companies in the banking sub-sectoryears 2017-2019. The results show that partially Corporate social responsibility has a significant effect on firm value with a prob value. Corporate social responsibility variable < critical probability value (a = 5%) of 0.027 <0.05, so that the Corporate social responsibility variable has a significant effect on firm value. The conclusion in the study accepts the hypothesis that corporate social responsibility has a significant effect on firm value.